Psychological Well-Being in Prison: An Early Adult Perspective - Putri, Pristiana Melina; Nurani, Gita Aulia (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
Prisoners tend to have mental issues that impair their psychological well-being and should find a means to achieve psychological well-being, especially if they are incarcerated. This study aimed to explore the personal experience of prisoners to find their psychological well-being. The participants in this study were inmates with diverse criminal histories. This study was conducted at one of the prisons in Central Java. In this study, the subject was identified utilizing a method of deliberate selection. The six respondents achieve psychological well-being by self-acceptance, exercising independence, improving themselves, keeping good relationships with others, and defining their surroundings, as determined by the findings of their interviews. Using member check and peer debriefing approaches, the validity of the data in this study was assessed. According to interviews conducted with social relations, the informants had difficulty adjusting to the new social environment upon entering prison. According to convicts, there was a need for adjustment to the new social environment in prison. However, according to all interviewers, the secret to socializing well while in prison is to adjust when speaking and communicating regularly.